Alveolar type 2 epithelial cell senescence and radiation-induced pulmonary fibrosis - Zhou, Shenghui; Zhu, Jiaojiao; Zhou, Ping-Kun; Gu, Yongqing (Frontiers in Cell and Developmental Biology, 2022)
Radiation-induced pulmonary fibrosis (RIPF) is a chronic, progressive respiratory tract disease characterized by collagen deposition. The pathogenesis of RIPF is still unclear. Type 2 alveolar epithelial (AT2) cells, the essential cells maintaining the structure and function of the lung tissue, are crucial for developing pulmonary fibrosis. Recent studies indicate the critical role played by AT2 cell senescence in initiating and progressing RIPF. Moreover, clearance of senescent AT2 cells and treatment with senolytic drugs efficiently improves lung function and radiation-induced pulmonary fibrosis symptoms. These findings indicate that AT2 cell senescence has the potential to contribute significantly to innovative treatment for fibrotic lung disorders. This review summarizes the current knowledge from basic and clinical research about the mechanism and roles of AT2 cell senescence in RIPF and points to clinical treatment prospects of targeting senescent AT2 cells.